Peran Pelatihan Kewirausahaan Syariah, Akses Permodalan, dan Manajemen Keuangan terhadap Keberlangsungan UMKM Halal - Amaliah, Amaliah (Benefits : Jurnal Ekonomi dan Pariwisata Internasional, 2026)
This study aims to analyze the role of sharia entrepreneurship training, access to capital, and financial management in supporting the sustainability of halal MSMEs in Indonesia. Halal MSMEs still face several obstacles, such as a lack of understanding of sharia entrepreneurship, limited access to sharia financing, weak financial management, and minimal readiness for halal certification. This study adopted a qualitative approach with a literature review method that utilized secondary data from scientific journals, reference books, government reports, and publications from relevant institutions. Data analysis was carried out qualitatively and descriptively through the steps of data reduction, data grouping, data presentation, and drawing conclusions. The research findings indicate that sharia entrepreneurship training can improve the knowledge and skills of MSME actors, access to sharia capital supports business development, while good financial management contributes to operational efficiency and business risk control. The combination of these three elements plays a role in increasing the productivity, competitiveness, and sustainability of halal MSMEs. This study is expected to serve as a reference for MSME actors and related parties in supporting the growth of sharia-based MSMEs in Indonesia.